A qualitative study and preliminary model of living with dementia and incontinence at home: beyond containment. (13th November 2021) - Murphy, Catherine; de Laine, Christine; Macaulay, Margaret; Avery, Miriam; Fader, Mandy
Abstract: Background: most people living with dementia (PLWD) will develop incontinence problems with associated harmful consequences. Well-contained incontinence is often the main treatment goal. It would therefore be expected that poorly contained incontinence would have a negative impact. Aim: to investigate differences in how well-contained or poorly contained incontinence impacts on the experience of living with incontinence for PLWD at home and their carers. Design: secondary analysis of a qualitative study. Methods: semi-structured interviews were undertaken with PLWD, carers and healthcare professionals (continence or dementia nurses). PLWD and carers were recruited via www.joindementiaresearch.nihr.ac.uk and via dementia/carer groups. Nurses were recruited via their employers. Interviews were recorded and transcribed verbatim. Framework analysis was used. Results: forty-five people (twenty-six carers, two PLWD, nine continence nurses and eight dementia nurses) participated. Despite poorly contained incontinence, some PLWD/carer dyads appeared relatively unaffected by incontinence. Conversely, one or both members of some dyads who achieved good containment found incontinence care highly challenging. Four themes were identified, together forming a preliminary model of incontinence containment and impact, as follows: Well-contained incontinence, lower negative impact Well-contained incontinence, higher negative impact Poorly contained incontinence, higher negative impact Poorly contained incontinence, lower negative impact Conclusion: reliable containment is an important goal for PLWD living at home and their carers, but it is not the only goal. Other factors, such as behaviours that challenge or carer coping strategies, can mean that even well-contained incontinence can have a negative impact. This paper proposes a preliminary model for evaluation.